PERFORMANCE AND PROSPECTS FOR CATTLE FARM BUSINESS FRIENDLY ENVIRONMENT IN WEST SUMATRA - Jefrey M Muis (Widyariset, 2015)
Most of the farmer groups managing cattle in West Sumatra have not achieved the business goals with little regard for the potential well and local resources that surround them and the lack of attention to environmental impact. The purpose of this study was to describe the performance of the enclosure management, feeding management, livestock waste management with respect to the concept of Green Marketing, and describes prospects for the cattle business in West Sumatra sustainable future. The research was conducted in 2012 in farmer groups Sejahtera Rambatan, Tanah Datar and groups Sejahtera Dua, in West Pasaman. The method used is the qualitative and quantitative approaches. The results of this study were (1) cage is best for beef cattle business is to facilitate the enclosure of communal feeding and cleaning cages. Need a good cage equipped breeding tank waste. (2) Management of by-product feed by utilizing skin cocoa plantations, palm leaf midrib and Solid largely able tosubstitute consentrate feed and forage with greater economic value. (3) By processing waste in the form of cattle faeces, cow urine and feed residue into organic fertilizer for farmers and provide benefits to cover the cost of feedproduction. (4) By applying the concept of Green Marketing in the cattle business is to provide economic benefits and environmental friendly.